Microplastics pollution in genetically connected populations of Holothuria forskali from south Bay of Biscay - Menéndez, Daniel; Álvarez, Almudena; Garcia-Vazquez, Eva; Ardura, Alba (Frontiers in Marine Science, 2024)
Sea cucumbers are increasingly demanded as seafood in different cultures around the world. Holothurians could be potentially exploited in southern Bay of Biscay (Iberian Cantabrian coast) where they are not fished yet. Recent studies show relatively high pollution by emerging pollutants like microplastics (MPs) in the region; perhaps the exposure of holothurians to those MPs may put them at risk. Here we analysed 60 samples of Holothuria forskali taken from the west and east of the Cape Peñas transition zone in different seasons. MPs were quantified from body wall tissue, and mitochondrial DNA sequences (16S and COI genes) were employed to determine population connectivity and infer replenishment capacity. Much higher MPs content in holothurian tissue than in water and sediments confirmed bioconcentration in this species. Significant differences between sampling locations were found, holothurian pollution being consistent with the occurrence of MPs sources like rivers, fishing ports and aquaculture. Genetic connectivity and no signals of diversity reduction in the most polluted samples suggest population replenishment capacity in H. forskali in the studied region. Results for a few samples of H. mammata from the same sampling points confirmed a higher MPs pollution at the west of Cape Peñas. According to these exploratory results, sea cucumbers seem to accumulate MPs especially in the western Cantabrian Sea. Further studies are recommended to understand the possible MPs threat for these holothurian species.